2009
DOI: 10.1080/10454440902908142
|View full text |Cite
|
Sign up to set email alerts
|

Cross-European and Functional Food-Related Consumer Segmentation for New Product Development

Abstract: . Functional Food emerged as a constant segment in the European

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 12 publications
2
23
0
Order By: Relevance
“…As such, prior nutrition knowledge level has been identified as an important factor influencing one's acceptance of functional foods (Sparke and Menrad, 2009); consumers who possessed higher level of nutrition knowledge reported higher intention to try functional foods (Annunziata and Vecchio, 2011;Ares et al, 2008). As for particular functional foods, it was found that the knowledge regarding to the health benefits of functional ingredients (i.e.…”
Section: Nutrition Knowledge and Health Claimmentioning
confidence: 99%
“…As such, prior nutrition knowledge level has been identified as an important factor influencing one's acceptance of functional foods (Sparke and Menrad, 2009); consumers who possessed higher level of nutrition knowledge reported higher intention to try functional foods (Annunziata and Vecchio, 2011;Ares et al, 2008). As for particular functional foods, it was found that the knowledge regarding to the health benefits of functional ingredients (i.e.…”
Section: Nutrition Knowledge and Health Claimmentioning
confidence: 99%
“…Furthermore, few segmentation studies use purchase behaviour in isolation, because it tends to result in limited, substantial and heterogeneous segments (for example, buyers and non-buyers of a product) that are probably not uniquely responsive to marketing efforts. Therefore, behaviour is sometimes measured in combination with other variables, such as purchase frequency (125) or motivations (107) to establish more diverse segments. Yet more often, past behaviour is used to describe segments rather than as a basis for market segmentation (102,126) .…”
Section: Past Purchasementioning
confidence: 99%
“…Second, to study the price in three different innovation types (conventional, organic, functional) and for three different market players (SME, MNC and retailers). The food brands are clearly differentiated by the technology, quality and production standards applied; and conventional food has the lowest innovativeness applied, whereas functional food has the highest (Verbeke 2006;Sparke and Menrad 2009;Hamzaoui-Essoussi and Zahaf 2012;Davcik 2013). In this process, this paper makes several contributions to the existing business literature.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to achieve this by estimating the organic and functional brands in comparison to conventional brands. Interested readers can assess this typology in detail from the food-orientated research articles (e.g., Sparke and Menrad 2009;Sorenson andBogue 2007, Hamzaoui-Essoussi andZahaf 2012;Davcik 2013).…”
Section: {Take In Tables 1 and 2}mentioning
confidence: 99%